Status of Wild Olive in Murree, Kahuta and Kotli Sattian National Park (Journal of Asian Development Studies, 2025)
This study investigates the ecological and socioeconomic significance of wild olive (Olea ferruginea) within Murree, Kahuta, and Kotli Sattian National Park. A comprehensive field survey was conducted using the fixed area plot method and quadrate sampling. Results showed considerable variability in tree distribution, with the number of trees per site ranging from 1 to 99 and a mean of 50.49 trees. The high standard deviation (29.16) and variance (850.25) indicated moderate clustering in certain areas. Tree ages ranged from 7 to 10 years (average: 9.29), with 47.5% of trees being 10 years old and only 3% being 7 years old, suggesting limited recent regeneration. Height distribution ranged from 6 to 14 feet (average: 9.13 feet), with most trees falling between 8–10 feet. Diameter at breast height ranged from 4 to 58 cm, with over 80% representing medium-sized trees, while larger specimens were scarce. Standard deviations and variance in growth patterns point to potential environmental or genetic influences. The study highlights a moderately healthy population with signs of regeneration; however, the low proportion of younger and larger trees emphasises the need for targeted conservation measures to support sustainable population dynamics and long-term ecological stability of the wild olive in the park.